The Role of Transformational Leadership, Work Environment on Job Satisfaction and Performance of Hospitals Employee During Digital Era - Santoso, Teguh Iman; Suharnanik, Suharnanik; Mendrofa, Yupiter; Putri, Ratna Komala (Jurnal Ilmiah Sumber Daya Manusia, 2023)
The purpose of this study was to analyze the relationship of transformational leadership on employee job satisfaction, work environment on employee job satisfaction, transformational leadership on employee performance, work environment on employee performance. This research is a quantitative causality study that aims to examine the influence of transformational leadership and environmental variables. work on employee performance through job satisfaction. In addition, the research also aims to predict and develop theory. Seeing the shape of the model and the number of endogenous variables that are more than one, the appropriate analysis technique used is structural equation modeling (SEM) based on variance or partial least squares (PLS) with smartPLS 3.0 software tools. The respondents of this study were 270 hospital employees who were determined by the simple random sampling method. Data were obtained from distributing online questionnaires via social media. The questionnaire was designed using a Likert scale of 1 to 7. The independent variables in this study were transformational leadership, work environment and job satisfaction. The dependent variable in this study is the performance of Hospitals Employee. The stages of data testing are validity test, reliability test, termination coefficient test and hypothesis testing. The results of this study indicate that transformational leadership has a positive effect on employee job satisfaction, the work environment has a positive and significant effect on employee job satisfaction, transformational leadership has an effect on employee performance, the physical work environment has an effect on employee performance.